DLQI‐R scoring improves the discriminatory power of the Dermatology Life Quality Index in patients with psoriasis, pemphigus and morphea. (16th October 2019) - Rencz, F.; Gulácsi, L.; Péntek, M.; Szegedi, A.; Remenyik, É.; Bata‐Csörgő, Z.; Bali, G.; Hidvégi, B.; Tamási, B.; Poór, A.K.; Hajdu, K.; Holló, P.; et al.
Summary: Background: The Dermatology Life Quality Index (DLQI) rates 'not relevant' responses (NRRs) as the item on the questionnaire having no impact on the patients' lives at all. The DLQI‐Relevant (DLQI‐R) is a recently developed scoring that adjusts the total score of the questionnaire for the number of NRRs indicated by a patient. Objectives: To compare the discriminatory power of the original and DLQI‐R scoring approaches in terms of absolute and relative informativity. Methods: Cross‐sectional data from 637 patients with morphea, pemphigus and psoriasis were used for the analyses. To assess absolute and relative informativity, Shannon's index and Shannon's evenness index were calculated for the 10 items on the questionnaire and for DLQI and DLQI‐R total scores. Results: Mean DLQI and DLQI‐R scores of patients were 6·13 vs. 6·91. In the subset of patients with NRRs ( n = 261, 41%), absolute informativity was higher with the DLQI‐R scoring for all eight items with NRR options in all three conditions. The DLQI‐R exhibited a better relative informativity in 8, 8 and 6 items in pemphigus, morphea and psoriasis, respectively. The DLQI‐R led to an improvement in average item‐level informativity in all DLQI score bands up to 20 points. Regarding total scores, the DLQI‐R produced both a higher absolute and relative informativity in all three conditions. Conclusions: In patients with morphea, pemphigus and psoriasis, DLQI‐R scoring improves the discriminatory power of the questionnaire by benefiting from the additional information in NRRs. DLQI‐R scoring may be useful both in clinical practice and research. A scoring chart has been developed to aid physicians with scoring. What's already known about this topic? The original scoring of the Dermatology Life Quality Index (DLQI) rates 'not relevant' responses as the item of the questionnaire having no impact on the patients' lives at all. DLQI‐Relevant (DLQI‐R) is a new scoring developed in 2018 that adjusts the total score of the questionnaire for the number of 'not relevant' responses indicated by patients. The discriminatory power of the DLQI‐R compared with the DLQI has not yet been investigated. What does this study add? In patients with psoriasis, pemphigus and morphea, DLQI‐R scoring improves the discriminatory power of the questionnaire by benefiting from the additional information in 'not relevant' responses. What are the clinical implications of this work? DLQI‐R scoring may help to more accurately quantify patients' health‐related quality of life both in clinical practice and research. A scoring chart has been developed to aid physicians with scoring. Abstract : Linked Comment: Bashyam and Feldman. Br J Dermatol 2020; 182:1082–1083 .